2015
DOI: 10.11648/j.jgo.20150305.11
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Levels of Sperm Parameters Impacting on Pregnancy Rate in an Intrauterine Insemination Programme

Abstract: Abstract:Objectives. Intrauterine insemination (IUI) is frequently used as a first line strategy in the treatment of male and unexplained infertility. Threshold levels of sperm parameters associated with IUI success are controversial. The aim of this study was to evaluate the influence of sperm parameters on the outcome of IUI. Study Design. A prospective observational study. Patients and methods. This study included 295 IUI cycles. All IUI cycles were preceded by ovarian superovulation with clomiphene citrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…Our result demonstrated that normal sperm morphology was significantly associated with pregnancy rates (p=0.032 before sperm processing and 0.007 after). These results also confirm the findings achieved by Jellad et al (8) and Kdous et al (32)…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our result demonstrated that normal sperm morphology was significantly associated with pregnancy rates (p=0.032 before sperm processing and 0.007 after). These results also confirm the findings achieved by Jellad et al (8) and Kdous et al (32)…”
Section: Discussionsupporting
confidence: 93%
“…Although several studies reported the effect of semen parameters on IUI success (7,10,14,32), Luco et al (12) failed to indicate such a relationship. A lack of agreement exists about the best semen parameters that can predict the possibility of pregnancy after IUI (13,32,33). Ruiter-Ligeti et al (10) evaluated the impact of semen processing on sperm parameters and pregnancy rates after IUI.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of several studies (15,18,23) that found no significant relationship between TMSC and IUI success (pre p=0.503 and post p=0.761 semen processing). Similar to our findings, Zadehmodarres et al (22), Koyun Ok et al (14), and Kdous et al (32) demonstrated that sperm concentration before and after preparation had no significant effect on IUI success (14,22,32). However, Dadkhah et al (30) did find such a relationship.…”
Section: Discussionsupporting
confidence: 89%
“…Although several studies reported the effect of semen parameters on IUI success (7,10,14,32), Luco et al (12) failed to indicate such a relationship. A lack of agreement exists about the best semen parameters that can predict the possibility of pregnancy after IUI (13,32,33). Ruiter-Ligeti et al (10) evaluated the impact of semen processing on sperm parameters and pregnancy rates after IUI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation